Edukasi Isi Piringku Dan Tepat Minum Suplemen Di Posyandu Al-Inayah Puskesmas Sambutan, Samarinda - Feiby Yohana Runtuwene; Icha Safitri; Taufiiqul Hakim; Victoria Yulita Fitriani (CV. Multi Kreasi Media, 2025)
Nutritional problems in Indonesia remain a serious issue, marked by the high prevalence of undernutrition alongside a growing number of overnutrition or obesity cases. The imbalance in dietary patterns and the public’s limited understanding of the importance of daily nutritional intake are the main contributing factors. Balanced nutrition plays a crucial role in supporting growth, development, and maintaining the immune system, particularly in children and adolescents. As part of a public health education initiative, the Ministry of Health introduced the “My Plate” (Isi Piringku) guideline, which illustrates the proper portion of healthy food on a single plate. In addition, the proper use of dietary supplements can help fulfill nutritional needs that are not met through daily food consumption, such as iron, folic acid, and vitamins. This health promotion activity aims to increase public awareness about the importance of balanced nutrition and the wise use of supplements. The educational session was conducted at Al-Inayah Integrated Health Post (Posyandu), under Sambutan Public Health Center, Samarinda City, through a session titled “The Secrets of My Plate and Proper Supplement Intake.” This activity is expected to raise community awareness toward adopting healthy eating patterns and supplement use as a preventive step against malnutrition and obesity.